(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Basically, teaching should include two main components, sending and receiving information. In the end, a teacher will try his best to impart knowledge as he has understood it. The use of innovative methods in educational institutions has the potential to not only improve education, but also empower people, strengthen governance, and accelerate efforts to achieve human development goals. of the country. With several educational options available to learners of the current generation, new trends seem to have emerged in the field of education that have completely changed the face of the traditional education system. Recent trends, methodologies and developments describe the important role of the education sector as a whole with internalizing the educational process, emphasizing quality over quantity, increasing adoption of technology, professional talent needs, etc.